2003
DOI: 10.1081/pfc-120018449
|View full text |Cite
|
Sign up to set email alerts
|

Influence of Ascorbic Acid Supplementation on the Haematological and Clinical Biochemistry Parameters of Male Rabbits Exposed to Aflatoxin B1

Abstract: This study was undertaken to evaluate the effectiveness of L-ascorbic acid (AA) in alleviating the toxicity of aflatoxin B1 (AFB1) in male New-Zealand white rabbits. Five rabbits (6 months of age and mean body weight 3.12 kg) per group were assigned to 1 of 6 treatment groups: 0 mg AA and 0 mg AFB1/kg BW (control); 20 mg AA/kg BW; 15 microg AFB1/kg BW; 15 microg AFB1 plus 20 mg AA/kg BW; 30 pg AFB1/kg BW; 30 pg AFB1 plus 20 mg AA/kg BW. Rabbits were orally administered their respective doses every other day fo… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

7
27
0

Year Published

2005
2005
2022
2022

Publication Types

Select...
9
1

Relationship

0
10

Authors

Journals

citations
Cited by 49 publications
(35 citation statements)
references
References 43 publications
7
27
0
Order By: Relevance
“…Similarly, Yousef et al (2003) observed that rabbits fed a diet enriched with antioxidants, such as ascorbic acid, had lower bilirubin levels after daily ingestion of aflatoxin B1.…”
Section: Discussionmentioning
confidence: 84%
“…Similarly, Yousef et al (2003) observed that rabbits fed a diet enriched with antioxidants, such as ascorbic acid, had lower bilirubin levels after daily ingestion of aflatoxin B1.…”
Section: Discussionmentioning
confidence: 84%
“…Vitamin C is an essential cofactor for many enzymes involved in diverse metabolic pathways [47]. Sahin et al [48] found that serum activities of SGOT and SGPT were not infl uenced by dietary vitamin C. Also, Yousef et al [49] and Yousef [50] found that rabbits treated with vitamin C did not show any changes in the activities of AST and ALT. Th is is in accordance with our results showing that vitamin C had no signifi cant eff ects in prevention against liver damages in Cd intoxicated rats.…”
Section: Discussionmentioning
confidence: 99%
“…It is known that liver is the pivotal organ which is responsible for the secretion of majority of serum proteins and decrease in protein biosynthesis and also reduced secretion due to the ability of aflatoxin to for abducts with DNA and RNA will decrease the concentration of serum proteins. Aflatoxins have previously been shown to lower the total protein concentration in serum of pigs, 35 rabbits 36 and broilers. 37 It is well known that leakage of hepatic housekeeping enzymes namely ALT (normal range in mice: 17-77 U/L) and AST (normal range in mice: 54-298 U/L) 38 serve as biochemical indices of hepatocellular damage and recovery offered by therapeutic agents indicates hepatoprotection.…”
Section: Discussionmentioning
confidence: 99%